The tissue distribution of T lymphocytes expressing different CD45 polypeptides. - Janossy, G; Bofill, M; Rowe, D; Muir, J; Beverley, P (1989)
The distribution of T lymphocytes expressing the different polypeptides of the leucocyte common antigen (LCA) family detected by CD45R and UCHL1 antibodies has been studied in normal lymphoid tissues. In the thymus most cortical thymocytes express UCHL1 and co-express CD4 and CD8. The more mature membrane CD3+ (mainly medullary) T cells are heterogenous and may express both UCHL1 and CD45R weakly or be restricted to display CD45R or UCHL1 alone. In the medulla both the CD45R+ and UCHL1+ subpopulations contain single positive CD4 and CD8 cells. In tonsils, germinal centre T cells are almost exclusively UCHL1+, CD4+ and a proportion also express HNK-1 (Leu 7) antigen. In the paracortical areas approximately equal numbers of CD45R+ and UCHL1+ cells are found but these separately occupy nests of cells containing one or the other type. Again, both CD45R+ and UCHL1+ cells include single CD4+ and CD8+ lymphocytes. A small proportion (less than 5%) of strongly CD45R+, UCHL1+ double-stained cells are also seen, and these probably represent recently activated lymphocytes. In the gut, small clusters of such strongly double-labelled cells are in the submuscular mucosae while cells of the lamina propria are almost exclusively UCHL1+. Many intra-epithelial lymphocytes are only weakly positive or negative for UCHL1 and appear to be CD45R-. These results are consistent with the view that expression of different CD45 polypeptides identifies successive stages of thymocyte-T-cell maturation and that following their thymic education, unprimed T lymphocytes are CD45R+, while primed memory T cells are UCHL1+. These populations occupy different microenvironments.